1992
DOI: 10.1111/j.1365-2796.1992.tb00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a meat‐free diet on the urinary excretion of 3‐methylhistidine and creatinine in chronic renal failure

Abstract: Urinary excretion of 3-methylhistidine has been proposed as an index of internal protein breakdown provided that the intake of exogenous 3-methylhistidine (meat) is excluded. To evaluate the potential use of 3-methylhistidine in the metabolic assessment of patients with advanced renal failure, we studied a group of 11 patients with markedly reduced renal function who were put on a meat-free diet (the protein intake was kept constant). Steady-state plasma concentration and urinary excretion of 3-methylhistidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…In the present study, higher plasma 3-MH and 3-MH/Crea were found in frail and pre-frail participants compared to robust participants, assuming an elevated muscle protein turnover in these participants. Due to its renal excretion, the plasma 3-MH concentration is linked to the kidney function [20,29,30]. In the present study, we normalized plasma 3-MH concentrations to the eGFR (3-MH/eGFR ratio) to surpass kidney function limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, higher plasma 3-MH and 3-MH/Crea were found in frail and pre-frail participants compared to robust participants, assuming an elevated muscle protein turnover in these participants. Due to its renal excretion, the plasma 3-MH concentration is linked to the kidney function [20,29,30]. In the present study, we normalized plasma 3-MH concentrations to the eGFR (3-MH/eGFR ratio) to surpass kidney function limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Meat and fish should not be consumed for about 24 hours prior to blood samplings since they can influence 3-MH plasma concentrations in humans [27,28]. Plasma 3-MH concentration depends on the kidney function [20,29,30], which decreases with age [31,32] and can be expressed by the estimated glomerular filtration rate (eGFR) [33]. We suppose that plasma 3-MH concentrations might be influenced by medication intake and multi-morbidity since frailty is related to multi-medication [34,35,36] and associated with multi-morbidity [37].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, LBM-CK should be the preferred method for use in clinical practice. However, it is important to note that creatinine generation rate is affected to a large extent by dietary meat intake as well as by body muscle mass (2,19). Therefore, the use of the creatinine kinetics method will possibly lead to underestimation of lean body mass in Chinese subjects, a population that has a low dietary meat intake.…”
Section: Discussionmentioning
confidence: 99%
“…3 These ants are found in the tropics and subtropics approximately between latitudes 33 N and 44 S, including regions of Texas and Louisiana. 4 Leaf-cutting ants are usually red-brown in color with 11-segmented antennae, 3 pairs of thorax spines, and a 2-segmented petiole (narrow waist). Nests are made from soils and can extend up to 1200 m 2 in surface area and more than 7 m deep.…”
Section: Leaf-cutter Ants In Wound Closurementioning
confidence: 99%
“…2,3 During exercise, the production of creatinine is increased, 3 and creatinine is low in individuals on meat-free diet. 4 In all these situations, estimation of GFR will be misleading. The Modification of Diet in Renal Disease and CKD-EPI equations are mainly used for patients with chronic kidney diseases.…”
mentioning
confidence: 99%